Tumor Growth Dynamics: Dietary Fish Oil Induced Inhibition of Human Breast Carcinoma Growth, A Phenomenon of Reduced Cellular DNA Synthesis or Increased Cell Loss? - J Gonzalez Michael; Duconge Jorge (Journal of Neoplasms, 2017)
Diets high in unsaturated fatty acids, especially those containing high levels of linoleic acid, e.g., corn oil, enhance mammary gland tumorigenesis in experimental animals. In contrast, diets high in long-chain polyunsaturated fatty acids such as eicosapentaenoic (EPA) and docosahexaenoic (DHA), e.g. menhaden oil, appear to have a suppressive effect on this tumorigenic process. Many mechanisms have been proposed to explain the tumor inhibitory action exerted by menhaden oil and other fish oils, e.g., differences in prostaglandin metabolism, energy efficiency, alterations of the immune system, changes in lipid peroxidation, etc. Fundamental to a mechanistic understanding of this phenomenon, however, is an understanding as to whether or not the tumor inhibitory activities of dietary fish oil is mediated via an inhibition of tumor cell proliferation or mediated via an enhancement of tumor cell loss. Whether the amount of dietary fat or the type of fat effects mammary tumorigenic processes, via an effect on tumor cell proliferation or tumor cell loss, has not been clearly established. In the studies described in this communication, three methods were utilized to study tumor cell proliferation, i.e., H3-thymidine autoradiographic analysis, 5-bromo 2'-deoxyuridine (Brdu) flow cytometric analysis, and proliferative cell nuclear antigen (PCNA) flow cytometric analysis. Two methods were used to study tumor cell loss, i.e., a determination of the I125Urd tumor emission rate and a determination of a cell loss factor from the formulas of Steel and Begg. The tumor examined was the human breast carcinoma cell line MDA- MB231 maintained in athymic nude mouse. No significant difference in cell proliferation between carcinomas of mice fed a high corn oil diet (20% w/w) and a diet high in fish oil (19% menhaden oil, 1% corn oil). In contrast, a significant (p<0.05) increase in the rate of I125Urd emission rate and cell loss factor from the carcinomas in the fish oil fed mice compared to the corn oil fed mice was observed. In summary, the decreased tumor volume in the human breast carcinomas maintained in athymic nude mice fed a fish oil diet as compared to those fed a corn oil diet, appears to be due, at least in part, to an increased rate of carcinoma cell loss rather than a decreased rate of carcinoma cell proliferation.
Keywords: Tumor growth